A Qualitative Study on the Implementation of Preconception Care in Preparation for Parenthood for Prospective Married Couples at Tanjung Tiram Community Health Center - Siti Nurul Fadhilah Sari; Santi Widya Purba; Martaulina Sinaga (International Journal Of Health Science, 2025)
Preconception care is a crucial component of reproductive health services aimed at preparing couples, especially prospective brides and grooms, for a healthy pregnancy and responsible parenting. This qualitative study used a phenomenological design to explore the implementation of preconception care for parenthood preparation among engaged couples at Tanjung Tiram Public Health Center. Data were collected through in-depth interviews with 13 participants, including 3 couples and 7 individual women. Thematic analysis revealed several key themes: initial knowledge, perceived benefits, sources of information, access readiness, the role of healthcare workers, barriers and support, and expectations. The findings show that most participants understood preconception care as physical check-ups but lacked awareness of its importance in educating for psychosocial readiness and childrearing. Although healthcare workers provided basic services and some counseling, the educational aspect on parenting and emotional preparation was insufficient. This study highlights the need for comprehensive preconception education that includes mental, social, and parenting preparation. It implies that preconception services should go beyond screening to include structured and culturally relevant health promotion, especially in rural areas like Tanjung Tiram.